Stress and coping strategies of patients receiving chemotherapy at Hospital Universiti Sains Malaysia - Ismail, Hasnida (Universiti Sains Malaysia, 2016)
Stress is defined as a relationship between the person and the environment that is appraised by the person as taxing or exceeding his or her resources and endangering his or her well-being. While, coping strategies defined as constantly changing cognitive and behavioral efforts to manage specific external and/or internal demands that are appraised as taxing or exceeding the resources of the person. The purpose of this study was to study the relationship between stress and coping strategies of patient receiving chemotherapy at Hospital Universiti Sains Malaysia (Hospital USM). A cross-sectional survey was using a set of self-administered questionnaire from the combination of Perceived Stress Scale and Ways Coping Strategies. A total of 110 respondents were involved in this study. Data was analyzed using SPSS version 22.0 and Chi-square test was used to analyze descriptive data. All the respondent involved in this study were from ward 1 Timur Depan, 3 Selatan, and Radiotherapy and Oncology Department (NROD) in HUSM, age ranged from 18 to 85 years old (M =51.82, SD = 15.086), which shows majority of female patients with 71 (64.5%) and monthly income RM501-RM2000 have the highest participant which is 41 (37.3%) from the total participants. This study revealed that there was a significant association between the level of stress and coping strategies (p=0.002) and there were no significant association between selected demographic data (age (p=0.068), gender (p=0.662), and monthly income (p=0.094) with level of stress. Cancer patients undergoing chemotherapy experienced moderate level of stress symptom. However different coping strategies were adopted to cope with their illness, chemotherapy treatment, practical and family problems, emotional and physical symptoms. In future research, investigation of interactions between the impact of individual coping strategies and specific stressors will reveal more about the dimensionality, as well the nature of coping in general.